Let my people go surfing : the education of a reluctant businessman, including 10 more years of business unusual - Chouinard, Yvon, 1938- (Penguin Books, 2016)
In his long-awaited memoir, Yvon Chouinard-legendary climber, businessman, environmentalist, and founder of Patagonia, Inc.-shares the persistence and courage that have gone into being head of one of the most respected and environmentally responsible companies on earth. From his youth as the son of a French Canadian blacksmith to the thrilling, ambitious climbing expeditions that inspired his innovative designs for the sport's equipment, Let My People Go Surfing is the story of a man who brought doing good and having grand adventures into the heart of his business life--a book that will deeply affect entrepreneurs and outdoor enthusiasts alike.